Longitudinal assessment of syringomyelia in Pomeranians - Santifort, Koen M.; Carrera, Ines; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2024)
Chiari-like malformation (CM) and syringomyelia (SM) in dogs are linked to a great number of (owner-reported) clinical signs (ORCS) suggestive of pain. Aging was associated with an increased risk of having SM in several studies. However, there are only a few longitudinal studies that assess the presence and severity of CM/SM over time in CKCS dogs and progression of SM was linked to progression of clinical signs. The aim of this study was to investigate ORCS, CM/SM classification, and quantitative syrinx parameters in relation to progression of time (age) within individual Pomeranians. Pomeranians with or without ORCS and with or without diagnoses of CM/SM were included that had undergone two (or more) MRI studies of the craniocervicothoracic region between January 2020 and June 2023. Classification of CM/SM and quantitative syrinx measurements were performed. Absolute values as well as ratios for syrinx height, width, and cross-sectional area were included for analysis. A total of 19 Pomeranians were included in the study, of which 11 were male (58%) and 8 were female (42%). The median age at the time of MRI1 was 26 months (range 7-44 months). The median scan interval was 26 months (range 11-49 months). Eleven dogs (58%) were presented with ORCS at the time of MRI1, whereas the other 8 dogs (42%) had no ORCS at that time. At the time of MRI2, there were 17/19 dogs (89%) with ORCS and 2/19 dogs without ORCS (11%). Dogs were significantly more likely to have ORCS at MRI2 than MRI1 (p = 0. 0411). There was no significant difference between CM/SM classification at the time of MRI1 and MRI2. Significant differences were found between MRI1 and MRI2 for syrinx height (based on transverse images) (absolute value and ratio P = 0.0059), syrinx width (absolute value P = 0.1055, ratio P = 0.0039), and syrinx cross sectional area (absolute value P = 0.0195, ratio P = 0.0217). There are differences in the presence or absence of ORCS as well as quantitative syrinx measurements in Pomeranians at different ages. This finding supports that longitudinal changes occur in the SM status of Pomeranians.